Investigation on Performance Evaluation of Corrugated Low Finned Tubes Oriented for Energy Saving. Issue 1 (June 2020) - Ren, Bin; Pu, Zhe; Tang, Xiaoying; Si, Sun; He, Aini; Lu, Hongliang
Abstract: Heat exchangers are the energy facilities that exchange heat in process industries.Corrugated low finned tube is a kind of helically corrugated tube with trapezoidal shape groove. In this paper, the comparison approach is adopted to evaluate the overall performance of corrugated low finned tubes. The heat transfer and friction factor correlations were firstly introduced. Then the overall performance was evaluated for the identical pressure drop and identical pumping power. Finally, the performance evaluation criteria were fitted as the function of Reynolds number, Prandtl number, pitch to diameter ratio and rib height to diameter ratio. The results showed thatboth the evaluation factors at identical pumping power and at the identical pressure drop are greater than 1.0 over the entire Reynolds number for all the enhanced tubes, indicating that the enhanced tubes have the second best performance oriented from energy-saving.